Prediction of high- and low-risk multiple myeloma based on gene expression and the International Staging System - Kuiper, Rowan; van Duin, Mark; van Vliet, Martin H.; Broijl, Annemiek; van der Holt, Bronno; el Jarari, Laila; van Beers, Erik H.; Mulligan, George; Avet-Loiseau, Hervé; Gregory, Walter M.; Morgan, Gareth; Goldschmidt, Hartmut; et al. (Blood, 2015)
Key Points. Combination of ISS and the EMC92 gene classifier is a novel clinically applicable risk classification for survival in multiple myeloma.ISS has clea